The profile of students HOTS at Malang, Indonesia in responding to higher-thinking biology questions - Ahmad Fauzi; Azizul Ghofar Candra Wicaksono (Biosfer: Jurnal Pendidikan Biologi, 2021)
Higher Order Thinking Skills (HOTS) is one of the primary 21st-century skills that Indonesian schools have not optimally developed. The present study was aimed at 1) presenting the profile of students’ HOTS in Malang and 2) investigating the influence of grades on students’ HOTS. This quantitative study involved 559 students from 18 schools in Malang municipality as the participants. The data were collected using ten essay questions as the instrument and analyzed through descriptive statistics and one-way ANOVA as the data analysis techniques chosen in this study. This study revealed that first, the students of Junior High School in grades VII, VIII, and IX at Malang acquired a low level of HOTS. Second, the students of Senior High School performed an excellent level of HOTS. Third, there was a significant influence of the student's grades to the level of the students’ HOTS in which senior high school students accomplished a higher level HOTS than junior high school students. Therefore, to improve this essential skill, the students in Indonesian schools should be given as much exposure to teaching and assessment based on HOTS.